N-FRACTIONAL CALCULUS OPERATOR METHOD TO THE EULER EQUATION - Yilmazer, R.; Ozturk, O. (Petrozavodsk State Univ, 2018)
We can obtain the explicit solutions of the Euler equation by using the fractional calculus methods. So, we apply the N operator method in the fractional calculus to solve this equation in this paper. We take advantage of some results of previous studies related to the fractional calculus.
Keywords: fractional calculus; Euler equation; ordinary differential equation